(untitled) (International Journal of Engineering Sciences & Management Research, 2021)
Purpose: Starting from in-depth research of the existing literature, the purpose of this research is to identify the main drivers that can guarantee not only survival but also the growth of independent (freelance) professionals. The case of professional accountants and auditors is of particular interest because bookkeeping is mandatory by law, and it is heavily affected by technological innovations and changes in the labor market. Methodology: Qualitative Analysis, Explorative Research Findings: The necessary skill set required for professionals is extremely complex. Regular updates, new qualifications, and skills are vital to ensure survival in the market, especially in comparison with large service companies (i.e., the so-called big-fours) because they allow independent professionals to compete on tailored and specific services. Implications for theory and practice: The identification of the qualifications’ required skills for independent professionals is of the highest interest not only for the professionals themselves but also for the higher education sector which must adapt to the new demands and needs of the market. Universities, in particular, must update their offer, increasingly aimed at convergence towards the preparation of highly qualified and specialized professionals. Originality and value: Compared to other research, this article focuses on independent professionals rather than big accounting and audit firms. Indeed, independent freelance professionals represent a highly qualified niche often forgotten by the analysis determined by academic research.